Experimental Study on Direct Tensile Properties of Cemented Paste Backfill - Guo, Lijie; Peng, Xiaopeng; Zhao, Yue; Liu, Guangsheng; Tang, Guoxing; Pan, Andrew (Frontiers in Materials, 2022)
Cemented paste backfill (CPB) has been increasingly utilized in mines for efficient mineral obtaining and regional ground support. To guarantee the work performance, the mechanical properties of CPB have long been a study focus of researchers. But in terms of the tensile strength of CPB, the research progress is limited, mainly because of the lack of appropriate test method due to the lower nature of CPB in tension. Therefore, instead of the conventional splitting indirect tensile strength test method, a new direct tension test method, which utilize the specifically designed compression to tension load converter (CTLC) and dog-bone shaped specimen, has been applied to study the direct tensile properties of CTB. In this study, the direct tensile strength (DTS) of 47 CPB mix designs were measured using CTLC, and the unconfined compressive strength (UCS) of the corresponding mix design was also tested. The experimental results showed that the increase in binder content, solid mass content, and curing period leaded to higher CPB direct tensile strength and the CPB DTS was most sensitive to binder content. Furthermore, the influence of slurry mass solid content on CPB tensile strength was not linear. The influence of binder content became increasingly notable with the increase of solid content, especially for binder content after 75%. The effect of the curing period was found to be rather marginal due to the decreasing amount of un-hydrated cementitious materials left with the increase of the curing period. Overall, the DTS generated using dog-bone specimens and CTLC apparatus are valid for better mine backfill designs. Finally, a linear correlative between UCS and DTS with a formula in the form of σDT (DTS) = 0.171 σc (UCS) was obtained, and the correlation was sufficient for further calculation of DTS using measured UCS.